Long-term Anti-inflammatory and Antihistamine Medication Use and Adult Glioma Risk - Scheurer, Michael E. (Cancer Epidemiol Biomarkers Prev, 2008)
A personal history of asthma or allergy has been associated with a reduced risk for adult malignant gliomas. Recent reports on the use of nonsteroidal anti-inflammatory drugs (NSAID) and the presence of risk alleles in asthma susceptibility genes showed similar inverse associations. To further explore the relationship between immune mediators and gliomas, we examined the use of NSAID and antihistamines, history of asthma or allergy, and infection in 325 glioma cases and 600 frequency-matched controls from the metropolitan area of Houston, TX (2001–2006). The regular use of NSAID was associated with a 33% reduction in the risk for glioma, suggestive of possible antitumor activity. Surprisingly, regular long-term antihistamine use among those reporting a history of asthma or allergies was significantly associated with a 3.5-fold increase in the risk for glioma. Similar to previous reports, cases in our study were less likely to have reported asthma, allergy, or a history of a number of viral infections (chickenpox or shingles, oral herpes, and mononucleosis) than controls. We therefore speculate that the observed positive association with antihistamine use may reflect an alteration of protective immune factors in susceptible individuals. Our results lend additional support for an important but unknown link between malignant brain tumors and immune mediators.